Intra-African trade integration - Cisse, Fatou; Kurtz, Julie E.; Odjo, Sunday P. (International Food Policy Research Institute, 2020)
This chapter aims to shed light on those questions through the calculation of simple trade indicators, namely the export similarity index, trade complementarity index, and regional trade intensity index, as well as assessing the impact of tariffs and examining the costs of nontariff measures (NTMs) at the intra-African level. Our results reveal that African economies mostly have dissimilar export patterns, suggesting possibilities for transborder trade expansion. However, complementarity between exports and imports among African countries is low, reflecting Africa’s colonial history of exporting raw commodity goods globally while importing processed goods, without developing a strategic web of regional supply chains within the continent. Yet despite limited complementarity in their current trading patterns, and high tariff and nontariff costs in some regions, the intensity of intraregional trade in Africa is higher than expected.